1997
DOI: 10.1242/jcs.110.19.2429
|View full text |Cite
|
Sign up to set email alerts
|

When rDNA transcription is arrested during mitosis, UBF is still associated with non-condensed rDNA

Abstract: The mechanisms that control inactivation of ribosomal gene (rDNA) transcription during mitosis is still an open question. To investigate this fundamental question, the precise timing of mitotic arrest was established. In PtK1 cells, rDNA transcription was still active in prophase, stopped in prometaphase until early anaphase, and activated in late anaphase. Because rDNA transcription can still occur in prophase and late anaphase chromosomes, the kinetics of rDNA condensation during mitosis was questioned. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(6 citation statements)
references
References 32 publications
1
3
2
Order By: Relevance
“…It is also possible that the increase happens at a certain stage of S-phase independent of the amount of DNA since we do not know the extent of S-phase of each cell. We did not observe a reduction in global cellular transcription through mitosis, unlike previous work in mammalian cells (Wansink et al, 1993;G ebrane-Youn es et al, 1997) and budding yeast (Clemente-Blanco et al, 2009). It is possible that undertaking mitosis without breaking down the nuclear envelope (Zheng et al, 2007) prevents the reduction in transcription observed in mammalian cells undertaking open mitosis.…”
Section: Discussioncontrasting
confidence: 95%
“…It is also possible that the increase happens at a certain stage of S-phase independent of the amount of DNA since we do not know the extent of S-phase of each cell. We did not observe a reduction in global cellular transcription through mitosis, unlike previous work in mammalian cells (Wansink et al, 1993;G ebrane-Youn es et al, 1997) and budding yeast (Clemente-Blanco et al, 2009). It is possible that undertaking mitosis without breaking down the nuclear envelope (Zheng et al, 2007) prevents the reduction in transcription observed in mammalian cells undertaking open mitosis.…”
Section: Discussioncontrasting
confidence: 95%
“…The dynamic equilibrium model assumes that the increase in the occupancy of RNA polymerases is due to a dynamic equilibrium between free polymerases associating with the DNA and detaching from the DNA. We did not observe a reduction in global cellular transcription through mitosis unlike previous work in mammalian cells [48,49] and budding yeast [50]. It is possible that undertaking mitosis without breaking down the nuclear envelope [51] prevents the reduction in transcription observed in mammalian cells undertaking an open mitosis.…”
Section: Discussion (969 Words)contrasting
confidence: 90%
“…Only a fraction of the 10 NORs in a diploid cell are active, the others being in a repressed, heterochromatic state (Grummt, 2003; Moss et al , 2007; McStay and Grummt, 2008). On entry into mitosis the nucleolus disassembles and rDNA transcription is silenced, but active NORs retain their open configuration and remain associated with the RPI transcription machinery, including UBF (Roussel et al , 1993, 1996; Jordan et al , 1996; Gebrane‐Younes et al , 1997; Grummt, 2003; Leung et al , 2004; Mais et al , 2005; Moss et al , 2007; McStay and Grummt, 2008). In our immunofluorescence experiments, examination of cells at different stages of mitosis showed that RasL11a and UBF formed prevalent foci on chromosome arms.…”
Section: Resultsmentioning
confidence: 99%
“…RasL11a co-localizes with UBF not only at nucleoli in interphase, but also on chromosomes in mitotic cells. UBF and the RPI machinery mark a subset of rDNA repeats on chromosome arms (NORs), which correspond to the active repeats (Roussel et al, 1993(Roussel et al, , 1996Jordan et al, 1996;Gebrane-Younes et al, 1997;Leung et al, 2004;Mais et al, 2005). The fact that RasL11a co-localizes on chromosome arms with either UBF (by immunofluorescence) or rDNA (by immuno-FISH) shows that RasL11a also marks active NORs in mitosis.…”
Section: Discussionmentioning
confidence: 99%